2019
DOI: 10.1177/1468796819877737
|View full text |Cite
|
Sign up to set email alerts
|

Which doctors do we trust? A vignette experiment of how gender and ethnicity influence trust

Abstract: Is people’s trust in doctors affected by their ethnicity or gender? It is often assumed that highly skilled migrants are protected from the worst effects of discrimination. Yet, they also report high degrees of discrimination. This study examines whether ethnic and gendered stereotypes influence trust in general practitioners in Norway. The question is investigated using a survey experiment. Respondents receive a brief resume of a general practitioner where the ethnicity and gender of the physician are randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In addition, HE Chinese female candidates modestly outperformed the other candidates (British and locals) in interpersonal skills but not in the other variables, for which no intersectional effects were observed. These results are consistent with previous findings (Alecu, 2019; Derous et al ., 2009), specifically, the studies which use less distant minority groups (e.g. McGinnity and Lunn, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In addition, HE Chinese female candidates modestly outperformed the other candidates (British and locals) in interpersonal skills but not in the other variables, for which no intersectional effects were observed. These results are consistent with previous findings (Alecu, 2019; Derous et al ., 2009), specifically, the studies which use less distant minority groups (e.g. McGinnity and Lunn, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…Interaction effects. In testing the SCM in Europe, Cuddy et al (2009) found several country stereotypes based on competence and warm differences, while some other studies found that national origin has a negative impact only in certain contexts (McGinnity and Lunn, 2011;Alecu, 2019;Derous et al, 2009), and for less prestigious ingroup members (Lewis and Sherman, 2003) and minorities (Ford and Mellon, 2020). This means that ingroup favouritism and outgroup discrimination can vary, and ingroup derogation and outgroup favouritism can be observed.…”
Section: Gender Premiummentioning
confidence: 98%
See 3 more Smart Citations